A flexible metal nano-mesh strain sensor with the characteristic of spontaneous functional recovery after fracture damage. Issue 34 (16th August 2022) - Zhao, Dongyang; Nie, Bangbang; Qi, Guochen; Li, Shijiao; Zhu, Qichen; Qiu, Jingjiang; Hsu, Yenya; Zhang, Yudong; Wang, Wen; Zhang, Qidong; Wei, Zonhan
Abstract : Developing flexible sensors with high sensitivity, a wide sensing range, and good stability is a challenge. Abstract : Developing flexible sensors with high sensitivity, a wide sensing range, and good stability is a challenge. By replicating the anodic aluminum oxide (AAO) hole structure, we proposed new strain sensors with Pt nano-mesh films embedded in polydimethylsiloxane (PDMS) films. The nano-mesh strain sensor exhibited high sensitivity (a gauge factor of 4500) and a sensing range as high as 90%. The resistance remained almost completely unchanged after 1500 loading/unloading cycles of 15% strain, demonstrating the high repeatability and stability of the sensor. In addition, even if the nano-mesh experienced an open circuit by overstraining, the sensor can still measure strain within 45% after recovery. The capability of spontaneous functional recovery after fractural damage considerably extends its service life. Finally, the nano-mesh strain sensors were worn on the wrist and neck to monitor wrist movement and throat vibration, respectively. Signals corresponding to swallowing, throat clearing, and letter pronunciation were clearly distinguished from the peak value and signal patterns. These results indicate that the metal nano-mesh strain sensors have great potential for applications in wearable devices, electronic skin, and flexible robotics.